2009
DOI: 10.1080/15388220903130155
|View full text |Cite
|
Sign up to set email alerts
|

Bullying of Students by Teachers and Peers and Its Effect on the Psychological Well-Being of Students in Jamaican Schools

Abstract: In this study, 225 Jamaican university students were asked to recall their bullying experiences at elementary and high schools. Being verbally humiliated, robbed, and beaten were the top three frequently-occurring experiences. Acts of bullying by peers and educators were compared for their impact on students' psychological well being. Educator but not peer bullying was associated with specific outcomes including students becoming oppositional, losing trust in others, and being depressed. Outcomes also differed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 23 publications
1
23
0
3
Order By: Relevance
“…Through our data, we have shown that our participants' narratives of becoming and being a leader are very much influenced by national level societal and cultural issues, experienced at a local level. The perceived issues identified in this study mirror those previously highlighted in the literature (see, for example, Baker-Henningham et al 2009;Morrison et al 2011;Pottinger and Stair 2009) and include a growing violence and gang culture in some of the case study schools, changing family structures, and declining shared value systems. However, the data also suggest that in becoming school leaders, the participants perceived that they had a strong sense of agency in attempting to challenge and change the social structures within the institutions they lead and in the surrounding local communities, which in turn, they hope, will have a lasting effect on the nation as a whole, particularly in relation to notions of citizenship and upholding traditional societal values (based on a strong Christian faith).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Through our data, we have shown that our participants' narratives of becoming and being a leader are very much influenced by national level societal and cultural issues, experienced at a local level. The perceived issues identified in this study mirror those previously highlighted in the literature (see, for example, Baker-Henningham et al 2009;Morrison et al 2011;Pottinger and Stair 2009) and include a growing violence and gang culture in some of the case study schools, changing family structures, and declining shared value systems. However, the data also suggest that in becoming school leaders, the participants perceived that they had a strong sense of agency in attempting to challenge and change the social structures within the institutions they lead and in the surrounding local communities, which in turn, they hope, will have a lasting effect on the nation as a whole, particularly in relation to notions of citizenship and upholding traditional societal values (based on a strong Christian faith).…”
Section: Discussionsupporting
confidence: 72%
“…It appears that some children can experience violence from a variety of sources, including corporal punishment at home and at school, and witnessing and involvement in violence with their peers. Relatedly, a prevalent culture of school bullying, both from peers and teachers, throughout the country has also been identified as negatively impacting on behaviour and psychological well-being amongst school children, with corporal punishment being identified as an accepted sociocultural norm in some areas of Caribbean society (Pottinger and Stair 2009). These and other social and cultural problems present many challenges for Jamaican school leaders, challenges which will be explored later in this paper.…”
Section: Ministry Of Education 2004) As In the Uk Science And Mathsmentioning
confidence: 99%
“…4 Boys appear to be more likely than girls to perceive themselves as victims of teacher maltreatment, a closely related construct to teacher bullying, 6,1719 and female students from families with a high socioeconomic status were shown to be victims of teacher verbal abuse less frequently. 20 Research investigating teacher verbal abuse of students has found that students with higher likelihoods of being verbally abused by teachers may comprise 15% of school children, and even as students change teachers from grade to grade, the probability of teacher verbal abuse remains relatively stable for these children.…”
Section: Introductionmentioning
confidence: 99%
“…For children who attend school regularly and face less social disadvantage, academic achievement tends to be the more important predictor of resilience than school engagement. For example, studies by Martin and Marsh (2008;2009) have shown that students who do not score high on contextual risk factors (their homes and communities are reasonably well functioning and financially stable) still experience normative challenges related to being in school during tumultuous periods of psychological and social development. All students, they explain, suffer stress related to writing tests, forming and ending of romantic relationships with other students, and transitioning between grade levels.…”
Section: Academic Achievement or School Engagement?mentioning
confidence: 99%
“…While the individual exercises some degree of personal agency, contextual factors influence which protective factors are the most important and when. Related threats to academic achievement are known to be bullying (Pottinger & Stair, 2009), the quality of relationships with teachers, principals, and staff (Morrison & Allen, 2007;Sharkey, You, & Schnoebelen, 2008), transitions between schools (McVey et al, 2003;Shortt, Hutchinson, Chapman, & Toumbouro, 2007), the student's emotional and psychological wellbeing (Tebes et al, 2007;Wong et al, 2009), the child's gender, race, and class (Ollis & Meldrum, 2008;National Crime Prevention Centre, 2009), and the availability of academic supports (Ager et al, 2011). Many of these factors have been addressed by school-based programs that remove threats to children's wellbeing while building the capacity of children to experience resilience.…”
Section: Resilience and Schools: An Overview Of Interventionsmentioning
confidence: 99%